WORK LIFE BALANCE AND NORMATIVE ORGANISATIONAL COMMITMENT OF SELECTED DEPOSIT MONEY BANKS IN A DO ODO/O TA LOCAL GOVERNMENT AREA, OGUN STATE (Intent Research Scientific Journal, 2022)
Balancing work and life is a constant challenge in today's world. Today's global marketplace necessitates unwavering 'work–life commitment' in the form of conflicting professional responsibilities. Many deposit money banks have been observed to be focusing on organising work related programmes in recent times to aid career accomplishment of their employees. Focusing only on work related programmes is somehow silently contradicting the notion of work–life balance, thus reduced employee normative commitment in the Nigerian deposit money banks. This study examined the effects of work-life balance (leave policies, flexible working arrangement, and welfare policies) on normative organisational commitment of selected deposit money banks in Ado-Odo/Ota Local Government Area, Ogun State. The study employed survey research design and selected one hundred and seventy (170) respondents from the population of three hundred and forty four (344) using simple random sampling method. Three hypotheses were tested using multiple regression method with the aid of SPSS version 25.0. The study results indicated that work-life balance indicators (leave policies, flexible working arrangement, and welfare policies) have positive and significant effects on normative organisational commitment. Thus, the study recommended that deposit money banks management should continuously embrace work-life balance measures such as leave policies, flexible working arrangement, and welfare policies in order to increase their employee normative commitment in the Nigerian deposit money banking industry.